Determination of ovality and wall thinning effects on B2 stress indices for pipe bends under in-plane closing bending moment. (February 2019) - Balakrishnan, S; Veerappan, AR; Shanmugam, S
The present work evaluates the combined effect of variable wall thickness and ovality on the B 2 stress index of bends under in-plane closing moment using finite element analysis. The material chosen is assumed to be elastic-perfectly plastic and large geometrical change effect was considered. Moment rotational curves were drawn for each bend model and from these curves the critical collapsing limit loads were determined by using the twice-elastic-slope method. The existence of ovality in the pipe bends has a major effect on B 2 stress index, while thinning has no effect. A general closed form equation for the B 2 stress index is presented for bends subjected to an in-plane closing moment.